The Language Project of the Centre and the integrated curriculum: two essential teaching tools in bilingual education - Cantero García, Víctor; Aarli, Gunn (Didáctica. Lengua y Literatura, 2012)
Through this collaboration, we try to emphasize the importance of development of our students of ESO language skills through two complementary tools pedagogical and didactical namely: language project of the centre and the integrated curriculum. In this paper, we propose to drive a set of linguistic and methodological arguments which will no doubt help understand the integrated curriculum makes sense and must be considered as the backbone of all courses and apprenticeships in L2. We have add-ins to amplify the sequences for students enrolled in non-linguistic area.
Keywords: language project; integrated curriculum; language skills; bilingual education